Peningkatan Kompetensi Guru Madrasah Ibtidaiyah Muhammadiyah dalam Pemanfaatan Media Pembelajaran Berbasis IT - Muamaroh, Muamaroh; Setyabudi, Titis; Mujazin; Saifudin; Nurhidayat, Nurhidayat; Enggarani, Nuria Siswi (Universitas Muhammadiyah Surakarta, 2024)
The aim of this community service activity is to increase the knowledge and skills of MIM Jatisasari teachers in using IT in learning at school. The problems faced by partners are: 1. Teachers still do not have the knowledge and skills in using IT and some teachers are even unable to create folders, create Google Drive, Google Forms and also cannot create PPT. 2. The school email address and teachers' email addresses are inactive and cannot be used. The number of participants was seven teachers. Instrument to obtain data through observation, interviews and documents. The process of implementing IT training is carried out through the partner problem analysis stage, training material creation stage, training implementation stage and evaluation stage. The results of this community service activity are: 1. Participants increase their insight into the use of IT as a learning medium. 2. Participants are able to create Google drive, Google form and PPT. 3. School and teacher email addresses can now be active and used again.